Penerapan Business Intelligence dan Visualisasi Informasi di CV. Mitra Makmur dengan Menggunakan Dashboard Tableau - Edgar Marvaro Riyadi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
CV. Mitra Makmur is a company engaged in aluminum and glass services located in the Cikarang industrial area. Currently this company has problems in managing their orders. From these problems, a lot of data can be taken to make a solution that can later be used for business purposes. These data are in the form of quotation data, offers, and other supporting data. With these data, a solution to this problem is proposed using a data analysis approach and information visualization through a dashboard based on a business intelligence roadmap. The output of this research is a dashboard that displays various visualizations that will later help business owners to see the overall desired information in managing orders every month. The analytical tools used are Tableau by utilizing several charts such as bar charts and histograms. With the user-friendly Tableau visualization, it is hoped that it can help business owners use these tools easily and can be run alone without using admin assistance and the like.